Relationship between different serum cartilage biomarkers in the acute response to running and jumping in healthy male individuals - Maren, Dreiner; Tobias, Munk; Frank, Zaucke; Liphardt, Anna-Maria; Anja, Niehoff (Scientific Reports, 2022)
The effect of physical activity on serum cartilage biomarkers is largely unknown. The purpose of the study was to systematically analyze the acute effect of two frequently used exercise interventions (running and jumping) on the correlation of seven serum biomarkers that reflect cartilage extracellular matrix metabolism. Fifteen healthy male volunteers (26 ± 4 years, 181 ± 4 cm, 77 ± 6 kg) participated in the repeated measurement study. In session 1, the participants accomplished 15 × 15 series of reactive jumps within 30 min. In session 2, they ran on a treadmill (2.2 m/s) for 30 min. Before and after both exercise protocols, four blood samples were drawn separated by 30 min intervals. Serum concentrations of seven biomarkers were determined: COMP, MMP-3, MMP-9, YKL-40, resistin, Coll2-1 and Coll2-1 NO2. All biomarkers demonstrated an acute response to mechanical loading. Both the COMP and MMP-3 responses were significantly (p = 0.040 and p = 0.007) different between running and jumping (COMP: jumping + 31%, running + 37%; MMP-3: jumping + 14%, running + 78%). Resistin increased only significantly (p < 0.001) after running, and Coll2-1 NO2 increased significantly (p = 0.001) only after jumping. Significant correlations between the biomarkers were detected. The relationships between individual serum biomarker concentrations may reflect the complex interactions between degrading enzymes and their substrates in ECM homeostasis.
CRIS-Team Scopus Importer:2022-04-29